Comparative investigation of ultrasonic cavitation erosion for two engineering materials - Volkov-Husović T.; Martinović S.; Alil A.; Vlahović M.; Dimitrijević B.; Ivanić I.; Pavkov V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Engineering materials are often exposed to various extremely harsh environments such as high temperatures and/or high pressure, thermal shocks, aggressive solutions, or cavitation erosion. The phenomenon of cavitation erosion is to be expected with flowing fluids where the parts of equipment include turbine blades, high-speed propellers, or pump parts. Such conditions usually cause surface degradation with defects in the form of pits and fractures, resulting in strength deterioration with a potential risk of failure, as well as shortening the lifespan of the materials requiring additional expenses for failure analysis, repair, and/or replacement of parts. This paper presents the main results of the cavitation erosion resistance study of two different engineering materials, 316L austenitic stainless steel and CuAlNi shape memory alloy (SMA). The cavitation erosion testing was carried out using an ultrasonic vibratory method with a stationary sample. The comparison of the behavior of these two materials under cavitation erosion conditions is shown based on the results of mass loss and analysis of the pits formed over time. Image analysis tools were used to quantify the surface damage levels. Detailed analyses revealed that the CuAlNi shape memory alloy (SMA) exhibited superior in terms of resistance and better behavior compared to stainless steel.